Heteroepitaxial passivation of Cs2AgBiBr6 wafers with suppressed ionic migration for X-ray imaging - Bo Yang (Nature Portfolio, 2019)
Ionic migration degrades not only the characteristics of halide perovskite solar cells, but also those of perovskite X-ray detectors. Here Yang et al. employ heteroepitaxial BiOBr to passivate Cs2AgBiBr6 double perovskite, which suppresses ionic migration and obtain high performance X-ray detectors.